Individual Differences in Discriminatory Fear Learning under Conditions of Ambiguity: A Vulnerability Factor for Anxiety Disorders? - Arnaudova, Inna; Krypotos, Angelos-Miltiadis; Effting, Marieke; Boddez, Yannick; Kindt, Merel; Beckers, Tom (Frontiers in Psychology, 2013)
Complex fear learning procedures might be better suited than the common differential fear conditioning paradigm for detecting individual differences related to vulnerability for anxiety disorders. Two such procedures are the blocking procedure and the protection-from-overshadowing procedure. Their comparison allows for the examination of discriminatory fear learning under conditions of ambiguity. The present study examined the role of individual differences in such discriminatory fear learning. We hypothesized that heightened trait anxiety would be related to a deficit in discriminatory fear learning. Participants gave US-expectancy ratings as an index for the threat value of individual CSs following blocking and protection-from-overshadowing training. The difference in threat value at test between the protected-from-overshadowing CS and the blocked CS was negatively correlated with scores on a self-report tension-stress scale that approximates facets of generalized anxiety disorder (DASS-S), but not with other individual difference variables. In addition, a behavioral test showed that only participants scoring high on the DASS-S avoided the protected-from-overshadowing CS. This observed deficit in discriminatory fear learning for participants with high levels of tension-stress might be an underlying mechanism for fear overgeneralization in diffuse anxiety disorders such as generalized anxiety disorder.